Development Of Smart Clothesline Prototype Based On Esp8266 Using Dimension Of Quality For Goods Analysis Method - Sulistiyasni; Lia Fitriatun Agustin; Muhammad Akbar Setiawan; Nur Alfi Ekowati (Engineering Faculty, UNSOED, 2026)
Global warming often causes the weather to become more unpredictable. Especially in Indonesia, currently the dry and rainy seasons often come unexpectedly. Unpredictable weather can also interfere with household chores, for example, drying clothes. An automatic clothesline control system is proposed as a solution to this problem. This research aims to build a prototype of a smart clothesline based on ESP8266 using the prototyping system development method and analyze its quality using the product testing method with product quality dimension attributes. The hardware used in the development includes Arduino Uno, NodeMCU ESP8266, rain sensor, infrared sensor, LDR sensor, and servo motor. Meanwhile, the software used is Blynk. The attributes assessed in the test include performance, durability, conformance to specifications, features, reliability, aesthetics, perceived quality, and serviceability. In other similar studies, the use of such product testing has never been done. The results of the study show that the smart clothesline prototype that was built has passed the product test with a product test value of 90.10.